The crisis caravan what's wrong with humanitarian aid? - Polman, Linda; Waters, Liz; Polman, Linda (New York Metropolitan Books, 2010)
Linda Polman takes us to war zones around the globe to show the often compromised results of aid workers' best intentions. It is time, Polman argues, to impose ethical boundaries, to question whether doing something is always better than doing nothing, and to hold humanitarians responsible for the consequences of their deeds. --from publisher description
Goma: a "total ethical disaster" -- Contract fever -- MONGOs -- Donor darlings -- Aid as a weapon of war -- Refugee warriors -- The hunger weapon -- When recipients call the shots -- Afghaniscam -- The logic of the humanitarian era -- Afterword: Ask them questions.
"First English edition published in the United Kingdom in 2010 under the title War games by Viking, London"--Title page verso.
Includes bibliographical references (pages [211]-220) and index.
Translation of: De crisiskaravaan.
Keywords: Disaster relief; Humanitarian assistance